INVENTARISASI JENIS TUMBUHAN PAKU (PTERIDOPHYTA) DI DESA PADANG PELASAN KABUPATEN SELUMA - Andika Pradipta; Rara Saputri; Seri Dewi Ami; Ahmad Walid (LP4MK STKIP PGRI Lubuklinggau, 2020)
This study aims to determine the types of ferns found in Padang Pelasan Village, Seluma Regency, Bengkulu Province. The research was conducted using a qualitative descriptive method, namely research by collecting data or words. Sampling Pteridophyta was done by the Cruise Method. Data obtained from ferns (Pteridophyta) was then identified by observing samples consisting of roots, stems, leaves, and spores. The ferns found were brought to the nail cultivation site and the planting process was carried out. Based on the research results, the results of the inventory of ferns in Padang Pelasan Village, Seluma Regency, found 30 species of ferns consisting of 12 families, namely 3 species of Blechnaceae, 2 species of Selaginellaceae, 1 species of Dennstaedtiaceae, 1 species of Gleicheniaceae, 6 species of Pteridaceae. 1 species of Lygodiaceae, 4 species of Schizaceae, 1 species of Davalliaceae, 1 species of Athyriaceae, 1 species of Aspleniaceae, 7 species of Polypodiaceae, and 1 species of Equisetaceae. The most dominating ferns are the Polypodiaceae with 7 species.